Algoritma Konversi Data Penjualan Microsoft Access Ke Mysql - Amrin Lubis, Muhammad (STKIP PGRI Sumatera Barat, 2014)
Zombie distro company is a distributor and retailer of garments based in the city of Padang. Currently the company has 14 business units spread across the city of Padang and Pekanbaru. During this time, the company has used to manage the Sales Application transaction data, DBMS used is Microsoft Access. Role of applications that manage the data of purchase, stock, distribution and sales business unit. Each business unit is also conductinga similar difference does not make a purchase to receive the goods but increase the mutation of goods from the head office. Business units everyday to send transaction data to the central office via email. Sales application to importand combineall the data so that it can be seen: inventory, daily sales, transfers and purchases. circum stancessuch as these continue to run for years so ittends to increase the database size to 40MB. Constraint that arises is diminishing Sales Application performance, the management wants to migratea database from Microsoft Access to MySQL. Data Conversion Algorithm Algorithm (AKD) is used to convert sales data. How it works AKD algorithm: (1) equating way connection because both are using different platforms using ODBC, (2) read the table one by one from the old database, (3) change the structure of thet able and write it to a new database recorder record, (4) repeat process 1, 2 and 3 until all thet ables in the old database to the new database migration. Users candirectly use the new database that contains the old sale stransaction data. The new database can be accessed by the new Sales Application.Keywords: algorithm, ODBC, conversion, migration